The rs2619566, rs10260404, and rs79609816 Polymorphisms Are Associated With Sporadic Amyotrophic Lateral Sclerosis in Individuals of Han Ancestry From Mainland China - Zhang, Jie; Qiu, Weiwen; Hu, Fan; Zhang, Xiong; Deng, Youqing; Nie, Hongbing; Xu, Renshi (Frontiers in Genetics, 2021)
The pathogenesis of sporadic amyotrophic lateral sclerosis (sALS) remains unknown; however, recent research suggests that genetic factors may play an important role. This study aimed at investigating possible genetic risk factors for the pathogenesis of sALS. In our previous study, we conducted a genome-wide association study (GWAS) in 250 sALS patients and 250 control participants of Han ancestry from mainland China (HACM) and retrospectively analyzed the previously reported candidate loci related with sALS including our GWAS investigated results. In this study, twenty-seven candidate loci that were most likely associated with sALS were selected for further analysis in an independent case/control population of 239 sALS patients and 261 control subjects of HACM ethnicity using sequenom massARRAY methodology and DNA sequencing. We discovered that the polymorphism rs2619566 located within the contactin-4 (CNTN4) gene, rs10260404 in the dipeptidyl-peptidase 6 (DPP6) gene, and rs79609816 in the inositol polyphosphate-5-phosphatase B (INPP5B) gene were strongly associated with sALS in subjects of HACM ethnicity. Subjects harboring the minor C allele of rs2619566 and the minor T allele of rs79609816 exhibited an increased risk for sALS development, while carriers of the minor C allele of rs10260404 showed a decreased risk of sALS development compared to the subjects of other genotypes. The polymorphisms of rs2619566, rs10260404, and rs79609816 may change or affect the splicing, transcription, and translation of CNTN4, DPP6, and INPP5B genes and may play roles in the pathogenesis of sALS roles in the pathogenesis of sALS.